Chemical investigation of soil and vegetation in the vicinity of brick kilns in Fateh Jang region of Pakistan - Begum, Shaheen; Adnan, Muhammad; Akhtar, Nosheen; Aziz, Muhammad Abdul; Yousaf, Saeeda; Tariq, Akash (Journal of Himalayan Earth Sciences, 2015)
Environmental pollution is a serious concern worldwide due to its adverse effect on both human and plants. Brick kilns generate black smoke, which contains trace elements in excess. Once such elements enter into the soil may cause toxicity to plants grown over such soils. The study objective was to assess the effect of black smoke generated from brick kilns on trace elements concentrations in soils and plants grown over such soils in the proximity of brick kilns at Fateh Jang, Rawalpindi. In total, 32 soil samples at a depth of 12 inches and associated plant samples were randomly collected in the vicinity of brick kilns towards all directions. Acid digestion of plants and soil samples was carried out along with heavy metals detection and analysis through Atomic Absorption Spectrometry. Among all heavy metals, cadmium was found to exceed the normal limits of Cd concentration in soil. Among all plant families Ranunculaceae was found to have highest Pb concentration. Euphorbiaceae family has shown high accumulation of Cu and Zn, while Fabaceae family was found good accumulator of Cd and Cr. It is concluded from the present study that smoke coming out of brick kilns contains different heavy metals. Except Cd all heavy metals were found to be in safe limits because some of the brick kilns were not functioning at the time of present research. Strict environmental laws should be implemented for brick kilns industries, plants with high accumulation potential of heavy metals are recommended to be grown in periphery of the kilns and poor quality of fuel may be replaced with less polluting fuels to avoid serious damage to animals, plants and human health.